Mobile Cloud-Privacy and Data Security in Healthcare Environment Using Cloudsim Simulator - Parameswari, R; Vani, K (International Journal of Engineering and Technology, 2018)
The advancement of telecommunication in the medical field makes the diagnosis and treatment of patients in a faster manner because the patient information are stored and maintained in an electronic storage device. But there are some issues related to physical data storage, privacy by accessing user data and security etc. With the help of the cloud computing these issues are reduced now. The mobile health care system can improve the quality of patient care and reduce a medical cost for both patients and hospitals. The simulation tool CloudSim is used to generate the data center details, providerâ€™s details and processing time.Â For the analysis, the cloud analyst tool can simulate the data center and others.Â The patient information in the Healthcare Information System (HIS) and Electronic Medical Records (EMRs) is stored in a data center or cloud platform in a secure manner.Â Â